KNOWLEDGE ISLAMIZATION MODEL OF ISMA'IL RAJI AL FARUQI'S PERSPECTIVES FACING THE EDUCATION CHALLENGES IN THE 21st CENTURY - Edison, Edison; Anwar, Abu; Mamla Saidah, Elbina (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2022)
This study aims to compile the work steps of the Islamization of science based on the Islamization model formulated by Isma'il Raji Al Faruqi. This qualitative approach research uses literature study method. This study identifies unhealthy symptoms in the aspects of scientific jurisprudence among Muslims who have not shown symptoms of recovery even in the 21st century. The results of the analysis then prompted the prioritization of the work plan for the Islamization of science in accordance with the ideas of Isma'il Raji Al Faruqi. The work plan begins with strengthening the five principle of unity and focuses on Islamization with a scientific integration model in the five fields of science, namely religious studies, educational management, research methodology, politics, and economics. Abstrak: Penelitian ini bertujuan menyusun langkah-langkah kerja Islamisasi ilmu pengetahuan berdasarkan model Islamisasi yang dirumuskan oleh Isma’il Raji Al Faruqi. Penelitian dengan pendekatan kualitatif ini menggunakan metode studi literatur. Penelitian ini mengidentifikasi gejala tidak sehat dalam aspek fikrah keilmuan di kalangan umat Islam yang belum menunjukkan gejala kepulihan bahkan hingga abad 21 ini. Hasil analisis tersebut kemudian mendorong penetapan prioritas rencana kerja Islamisasi ilmu pengetahuan sesuai dengan gagasan Isma’il Raji Al Faruqi. Rencana kerja tersebut dimulai dengan penguatan prinsip panca kesatuan dan fokus melakukan Islamisasi dengan model integrasi keilmuan pada lima bidang ilmu pengetahuan yakni studi agama, manajemen pendidikan, metodologi penelitian, politik, dan ekonomi.